Tai chi chuan exercises improve functional outcomes and quality of life in patients with primary total knee arthroplasty due to knee osteoarthritis. (May 2019) - Li, Liangtao; Cheng, Shihuan; Wang, Guodong; Duan, Guoqing; Zhang, Yuanmin
Abstract: Background and purpose: Postoperative rehabilitation plays an indispensable role for a successful total knee arthroplasty (TKA) and the optimal exercises programs are not known. A single-centre, single-blind, randomised controlled trial was designed to explore whether tai chi chuan (TCC) exercises can improve the functional outcomes and the quality of life (QOL) in patients with primary TKA due to knee osteoarthritis (OA). Materials and methods: One hundred seven participants with primary TKA for end-stage knee OA were enrolled from January 2014 to January 2017. Patients were treated for 12 weeks either with TCC exercises (intervention) or traditional physical exercises (control). Outcomes including western ontario and mcMaster universities arthritis index (WOMAC), 6-min walk test (6 MWT), knee range of motion (ROM), and short form (36) health survey (SF-36) were assessed. The adverse events related to TCC exercises or TKA were recorded. Results: Before the intervention, the two groups were comparable after examining the general descriptions of patients. Compared with the control group (CG), the TCC group (TG) had significantly better scores in the WOMAC physical function score, 6 MWT, SF-36 physical component score (PCS), and the mental component score (MCS) (P < 0.05) after the 12-week intervention. Nevertheless, there were no significant differences in WOMAC pain score and knee ROM. There were no adverse events related to the TCC exercise program. In the CG, three patients reported one fall each, but those falls did not lead to a further problem. Conclusion: The TCC exercises improve the physical function and the QOL in patients with primary TKA without additional risks. Highlights: Tai Chi exercises can improve the functional outcomes and the quality of life for patients with TKA. Tai Chi exercises as a mild exercise does not have negative side effects on patients with TKA. Tai Chi exercises seem to be a new form of postoperative rehabilitation exercises for patients with TKA.